Construction of Ultrathin S‐Scheme Heterojunctions of Single Ni Atom Immobilized Ti‐MOF and BiVO4 for CO2 Photoconversion of nearly 100% to CO by Pure Water. Issue 41 (9th September 2022) - Zhao, Lina; Bian, Ji; Zhang, Xianfa; Bai, Linlu; Xu, Linyao; Qu, Yang; Li, Zhijun; Li, Yuxin; Jing, Liqiang
Abstract: To rationally design single‐atom metal–organic framework (MOF)‐involving photocatalysts remains an ongoing challenge for efficient CO2 conversion. Here, cuppy microstructures, consisting of a Ti(IV)‐oxo node and three linked carboxylic moieties, in the single‐coordination‐layer Ti2 (H2 dobdc)3 MOF (NTU‐9) are exploited to immobilize abundant single Ni(II) sites (Ni@MOF). The coupling of Ni@MOF with BiVO4 (BVO) nanosheets by H‐bonding‐induced assembly process obtains wide‐spectrum 2D heterojunctions. The optimal heterojunction exhibits competitive performance and enables around 66‐fold CO2 conversion of that for BVO nanoparticles by pure water, with nearly 100% CO selectivity. The exceptional photoactivity is attributed to favorable S‐scheme charge transfer from BVO to MOF then to single Ni(II) sites. Noteworthily, single Ni(II) sites anchored by the Ti(IV)‐oxo node and vicinal carboxylic moieties serving as a unique local microenvironment (LME) are found to synergistically catalyze CO2 conversion. Specifically, the hydroxyl groups of carboxylic moieties can form H‐bonds with CO2 to promote its adsorption on single Ni(II) sites, and also can provide accessible protons to facilitate H‐assisted CO2 reduction. Moreover, the CO desorption and subsequent CO2 adsorption on single Ni(II) sites with LME is proved to be thermodynamically favored, and hence dominates the high CO selectivity. This work highlights the significance of modulating the LME of single atoms to rationally design photocatalysts for realizing carbon neutralization. Abstract : Wide‐spectrum heterojunctions are successfully fabricated by coupling single‐atom Ni immobilized single‐coordination‐layer NTU‐9 as a reformative reduction half semiconductor with 2DBiVO4 through H‐bonding induction, which represents a novel S‐scheme heterojunction photocatalyst model. Favorable charge separation and efficient catalytic sites of single Ni atoms with unique local microenvironment synergistically promote CO2 photoconversion, achieving up to 66‐fold conversion rate by pure water compared to reference BiVO4 nanoparticles, together with nearly 100% selectivity to CO without any H2 .